Editorial: Letter from the Editors - Heitmeyer, Wilhelm; Massey, Douglas S.; Messner, Steven F.; Sidanius, James; Wieviorka, Michel (International Journal of Conflict and Violence (IJCV), 2012)
Dear Reader, This issue of the journal focuses on the question of bullying prevention, with a collection of articles put together by Manuel Eisner and Tina Malti. We are very grateful to them for the hard work they put in as focus section editors – and in their contributions to the section. The open section this time takes us to North America for a study of identity and in-group superiority and Africa for a review of the question of youth and violence. The next issue, to appear in spring 2013, will feature a double focus for the first time, presenting collections on transitional justice and on qualitative research on prejudices. December 2012 Wilhelm Heitmeyer Douglas S. Massey Steven F. Messner James Sidanius Michel Wieviorka